Variabilité socio-écologique, crise du pastoralisme et résilience des Peuls pasteurs du Gourma rural (Burkina Faso) - Gabin Korbéogo (VertigO)
Combining empirical research and state of art on pastoral practices and regimes of animal ownership of pastoral societies in Africa and Burkina Faso in particular, this paper explores the strategies of resilience of Fulani pastoralists of rural Gourma in an environment marked by ecological variability, uses’ conflicts of natural resources and the integration of pastoral economy in global market. In order to cope with the effects of environmental imbalance and socio-economic change, Fulani herders react within strategies like pastoral mobility, commodification of animals through target selling for alternative investments in urban land property and rental housing. The multiplicity of adaptive management of the vulnerability of ecological and socio-pastoral change reflects the flexibility of the practical rationality of Fulani pastoralists of rural Gourma.